Parallel Optical Burst Switching (POBS) for Ultra-Dense WDM (U-DWDM) systems - Abdelouahab A.; Abbou F.M.; Ewe H.T. (2023)
Several different switching paradigms have been devised to transfer data over Wavelength-Division Multiplexing (WDM), such as Optical Circuit Switching (OCS) a wavelength-routed network, Optical Packet Switching (OPS), and Optical Burst Switching (OBS). Given that any optical switching strategy is mainly shaped by the advances in the optical technology, the optical communications systems must provide for the highest possible data rate. This paper introduces, as a variant of OBS, a new optical switching strategy for Ultra-Dense WDM (U-DWDM), named Parallel Optical Burst Switching (POBS). POBS simplifies the scheduling/switching algorithms and reduces, relatively, the number of control channels, which, in its turn, reduces the number of the Opto-Electrical / Electro-Optical converters needed in the core nodes. Furthermore, POBS simplifies the design of the burst segmentation techniques and service differentiation schemes, and the implementation of the Fiber Delay Lines (FDLs). In addition, the number of required switching elements and wavelength converters needed in the core nodes can be lowered with POBS, therefore, lowering the overall network cost, if the waveband switching is deployed. 2011 IEEE.